The relevance of traditional knowledge systems for ethnopharmacological research: theoretical and methodological contributions - Reyes-García Victoria (BMC, 2010)
Abstract Background Ethnopharmacology is at the intersection of the medical, natural, and social sciences. Despite its interdisciplinary nature, most ethnopharmacological research has been based on the combination of the chemical, biological, and pharmacological sciences. Far less attention has been given to the social sciences, including anthropology and the study of traditional knowledge systems. Methods I reviewed the literature on traditional knowledge systems highlighting its potential theoretical and methodological contributions to ethnopharmacology. Results I discuss three potential theoretical contributions of traditional knowledge systems to ethnopharmacological research. First, while many plants used in indigenous pharmacopoeias have active compounds, those compounds do not always act alone in indigenous healing systems. Research highlights the holistic nature of traditional knowledge systems and helps understand plant's efficacy in its cultural context. Second, research on traditional knowledge systems can improve our understanding of how ethnopharmacological knowledge is distributed in a society, and who benefits from it. Third, research on traditional knowledge systems can enhance the study of the social relations that enable the generation, maintenance, spread, and devolution of cultural traits and innovations, including ethnopharmacological knowledge. At a methodological level, some ethnopharmacologists have used anthropological tools to understand the context of plant use and local meanings of health and disease. I discuss two more potential methodological contributions of research on traditional knowledge systems to ethnopharmacological research. First, traditional knowledge systems research has developed methods that would help ethnopharmacologists understand how people classify illnesses and remedies, a fundamental aspect of folk medicinal plant selection criteria. Second, ethnopharmacologists could also borrow methods derived from cultural consensus theory to have a broader look at intracultural variation and at the analysis of transmission and loss of traditional ethnopharmacological knowledge. Conclusions Ethical considerations in the ethnopharmacology of the 21st century should go beyond the recognition of the Intellectual Property Rights or the acquisition of research permits, to include considerations on the healthcare of the original holders of ethnopharmacological knowledge. Ethnopharmacology can do more than speed up to recover the traditional knowledge of indigenous peoples to make it available for the development of new drugs. Ethnopharmacologists can work with health care providers in the developing world for the local implementation of ethnopharmacological research results.